Creep Deformation Characteristics and Damage Unified Creep Constitutive Model of Undisturbed Structural Loess Under Different Consolidation Conditions - Yuan Yuan; Hui-Mei Zhang; Zhao-Yuan Gou; Pan Wang (Buildings)
In the loess-filling project, the original structural loess under the filling will produce creep deformation under the isometric consolidation stress state, affecting the upper building’s safe construction and later operation. Therefore, studying the creep deformation characteristics of structural loess under different consolidation coefficients is significant. In this paper, the following results are obtained by combining test and theoretical analysis. In view of the structural loess under the filling, the triaxial creep test of undisturbed loess under different isometric consolidation coefficients, confining pressures and shear stress levels was completed, and the creep deformation law of structural loess was obtained. The creep characteristics of undisturbed loess are found to be diversified under different coefficients, confining pressures, and shear stresses, including initial instantaneous deformation, subsequent creep attenuation deformation, and final stable creep deformation. The damage creep constitutive model of undisturbed loess is established, taking the binary medium model as the framework, the cementation element adopts the Nishihara model, the friction element introduces the overstress model and considers the isometric consolidation effect, and the damage creep constitutive model of undisturbed loess is established. The theoretical model is obtained by determining the relevant parameters of the constitutive model. The theoretical curve is compared with the experimental curve and shows that the damage creep model established in this paper can better reflect the creep of structural loess under isometric consolidation conditions well. The research results can provide systematic theoretical support and an experimental basis for the deformation problems involved in the filling project in the loess area.